Firmware design for microcontrollers on EtherCAT network for quadruped robot motion control - Athiniotis, Stamatios (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Μηχανολογικών Κατασκευών και Αυτομάτου Ελέγχου. Εργαστήριο Αυτομάτου Ελέγχου και Ρυθμίσεως Μηχανών και Εγκαταστάσεων, 2018)
Modern motion control requires large data and resources from different devices, sensors and libraries, which must be recognizable and within reach, to be viable. EtherCAT is the fastest industrial Ethernet technology setting new standards for real-time performance and topology flexibility. When using an EtherCAT infrastructure for motion control, all hardware accessories and necessary motors - cables are easily connected to the system with minimum wiring compared to traditional methods. Thus, reducing clutter within the working area, the possibility of an accident that may be caused by loose cables and other loose fittings within the room decreases, making motion control far more manageable. Motion control solutions based on the EtherCAT framework are purpose-built for enhanced performance and come with immense advantages since machine automation becomes more cost effective with much better turn-around times and outputs. In this thesis, the development of an EtherCAT network of microcontrollers is introduced, describing the configuration process of a slave and all the implementation prerequisites. For the purpose of implementing EtherCAT technology, TwinCAT XAE (Visual Studio) is exploited to realize the master node in a Windows Operating System (OS). On the other hand, to materialize the slave nodes of the network, the LaunchXL – F28379D launchpad by Texas Instruments is used as the host Micro Controller Unit (MCU) along with FB1111-0141 by Beckhoff as the EtherCAT Slave Controller (ESC). The provided software (available for download) which is thoroughly explained within the second chapter, is fully operational and contains all required EtherCAT stack to implement an analogous network. It is assembled in such a way that no specific User Application is coded, therefore users may define the functionality of each node according to their needs. Subsequently, in the third chapter, the motion control via EtherCAT of Laelaps II quadruped robot is explained along with a description of its leg architecture and electrical system details. Each slave connected to the robot’s network (EtherCAT Control Tower Assembly) controls the motion of one leg, including the hip and knee motors, using elliptical shaped trajectories for its End Effector. Furthermore, the TwinCAT Scope View Tool is adumbrated enabling the data logging of EtherCAT variables for their post processing in Matlab. Finally, in the fourth chapter, the experimental validation of the exploited decentralized control theory of Laelaps II is appended, illustrating the response of all four legs in a fundamental test. The experimental process is described and a table containing all used parameters is provided before presenting the resulting figures of each joint. The overall procedure proves that the running stack is judiciously assembled, fully functional and prudent to be tested in higher velocities of the robot in the future.